Penser le corps-marchandise avec Alfred Sohn-Rethel - Fabrice Colomb (Recherches Germaniques)
This article analyzes the commodification of the human body with the help of Alfred Sohn-Rethel’s work, which clarifies two distinct processes. On the one hand, it shows that monetization is only possible by reducing reality to a quantity. On the other hand, it shows the extent to which the legitimization of this operation is contained in the same monetization. This article further addresses the case of biobanks and the blood industry in France, which illustrate the commodification of an originally non-capitalist reality. It also clarifies the way in which this process can be legitimized, starting with the rhetorical disinhibition of the relationship between money and bodies.